1954
DOI: 10.3382/ps.0330112
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Energy Requirements of Chickens

Abstract: T HE energy requirement of growing chicks has been studied in two widely different ways. One method is illustrated by the studies of Mitchell, Card and Hamilton (1931) who estimated the net energy requirements for maintenance and growth from the determination of basal metabolic rate and changes in body composition. Data of this kind have been of limited usefulness because of the lack until relatively recently of net energy values for poultry feedstuffs.The other method was used by Robertson, Miller and Heuser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
2

Year Published

1961
1961
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(40 citation statements)
references
References 5 publications
2
36
0
2
Order By: Relevance
“…It is interesting to note that feed intake was not inversely proportional to the energy level of the diet, as opposed to Hill & Dansky (1950, 1954. Therefore, birds that were fed 3,400 kcal and 3,600 kcal ME.kg -1 had higher (p<0.05) energy intake when compared to those receiving 3,200 kcal ME.kg -1 .…”
Section: Resultsmentioning
confidence: 82%
“…It is interesting to note that feed intake was not inversely proportional to the energy level of the diet, as opposed to Hill & Dansky (1950, 1954. Therefore, birds that were fed 3,400 kcal and 3,600 kcal ME.kg -1 had higher (p<0.05) energy intake when compared to those receiving 3,200 kcal ME.kg -1 .…”
Section: Resultsmentioning
confidence: 82%
“…It has been suggested that chicks are capable ofregulating their feed intake according to energy level (Hill and Dansky 1954) although growth is adversely Can. J. Anim.…”
mentioning
confidence: 99%
“…Sci. 682 923-930 (Sept. 1988) affected when low energy diets are used (Hill and Dansky 1954). Protein appetite is less well defined since broilers in a choice situation do not maintain their protein intake (Cowan and Michie 1977).…”
mentioning
confidence: 99%
“…The addition of energy to this ration improved both growth and efficiency of conversion. Hill and Dansky (1954) concluded that feed consumption was determined primarily by the energy level of the diet. Biely and March (1954) indicated that the addition of energy, in the form of added fat, may be advantageous in both chick and poult rations when relatively high levels of protein are fed.…”
Section: Review Of Literature Effect Of Dietary Energy On Protein Utimentioning
confidence: 99%